Prevalência de diabetes mellitus em indivíduos portadores de periodontite em uma área rural do Sul do Brasil - Tavares, Rodrigo da Cunha Rossignollo (2018)
The objective of this study is to evaluate the prevalence of patients with diabetes among the individuals diagnosed with periodontitis using a threshold level that allows identifying more severe cases with considerable extension in a rural area of the South of Brazil. Data from the sub-sample with 320 individuals aged 18 to 91 years of the sample representative of individuals aged 15 years or more among the rural population of Rosário do Sul. Data were collected from the sample through clinical, laboratory and structured questionnaires. Diabetes was diagnosed by examination of glycated hemoglobin. Periodontitis was diagnosed when ≥ 30% of the teeth had clinical attachment loss ≥ 5mm. Logistic regression model adjusted for body mass index was used to estimate odds ratio and confidence interval (95% CI). The prevalence of diabetes in individuals with periodontitis was 15.1%. After adjusting for body mass index, individuals with severe periodontitis had more chance to have diabetes (OR = 2.14; CI = 1.02 - 4.52). It was possible to conclude that severe periodontitis has an impact on glycemic levels causing an increase in these levels. This fact demonstrates that individuals with periodontitis had more diabetes mellitus prevalence.